Structural and luminescence investigations of Gd3+ - Er3+ doped in lithium aluminum borate glasses using XANES and EXAFS techniques. (May 2023) - Manyum, P.; Rittisut, W.; Mool-am-kha, P.; Ekwongsa, C.; Wantana, N.; Ruangtaweep, Y.; Popanao, M.; Rujirawat, S.; Yimnirun, R.; Kidkhunthod, P.; Prasatkhetragarn, A.; Kothan, S.; et al.
Abstract: The typical melt quenching technique was utilized to produce a possibly unique series of Gd 3+ and Er 3+ dual doped borate glasses with a composition of 25Li2 O–5Al2 O3 -XGd2 O3 -(69.0-X)B2 O3 -1.0Er2 O3 . The amorphous nature and information on chemical bindings of the materials were validated by using fundamental characterization techniques such as X-ray diffraction, Fourier transform infrared, X-ray absorption near-edge structure, and optical screening to identify their features (absorption, excitation, and emission). The refractive index of the glasses improves from 1.5487 to 1.628 as the concentration of Gd2 O3 increases. The optical absorption spectra of Er 3+ doped glasses were measured from the ultraviolet (UV) through the visible (Vis) and near infrared (NIR) ranges with varying Gd2 O3 concentrations in order to determine their optical properties. This luminescence was found to be predominant in photoluminescence spectra, which were obtained at an optimum doping Gd2 O3 concentration of 7.5 mol%. The impact of Er 3+ doping was assessed through photoluminescence, which exhibited a broad, intense NIR band at 1537 nm ascribed to the 4 I13/2 → 4 I15/2 transition of Er 3+ ions at λEx = 486, 526, 651, and 978 nm excitation, which exhibits outstanding increased intensity with the Er 3+ concentration until it reaches 1.0 mol %. A look at visible and near-infrared optical, it is observed that LAGd7.5BEr1.0 glass is a more potential candidate for photonic devices. Highlights: A new borate glasses with mixed Gd 3+ /Er 3+ dual doping was synthesized. The best concentration of Gd2 O3 was observed at 7.5 mol%. A detailed structural and optical properties of the Gd 3+ /Er 3+ doped effect on the borate glass have been investigated. Er2 O3 0.5 mol% is the quenching concentration confirmed by the photo-luminescence.